2020
DOI: 10.1002/glia.23831
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of Kir2.1 potassium channels depolarizes spinal microglial cells, reduces their proliferation, and attenuates neuropathic pain

Abstract: Spinal microglia change their phenotype and proliferate after nerve injury, contributing to neuropathic pain. For the first time, we have characterized the electrophysiological properties of microglia and the potential role of microglial potassium channels in the spared nerve injury (SNI) model of neuropathic pain. We observed a strong increase of inward currents restricted at 2 days after injury associated with hyperpolarization of the resting membrane potential (RMP) in microglial cells compared to later tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…It has been reported that K channel activation and hyperpolarization is critical for microglial motility [33,74]. In addition, spinal microglia reactivity is correlated with K channel activation in neuropathic pain [75,76]. Therefore, these results suggest that membrane hyperpolarization (associated with K channels) instead of depolarization in microglia may activate microglia, likely due to the increase of Ca 2+ driving force.…”
Section: Plos Biologymentioning
confidence: 70%
“…It has been reported that K channel activation and hyperpolarization is critical for microglial motility [33,74]. In addition, spinal microglia reactivity is correlated with K channel activation in neuropathic pain [75,76]. Therefore, these results suggest that membrane hyperpolarization (associated with K channels) instead of depolarization in microglia may activate microglia, likely due to the increase of Ca 2+ driving force.…”
Section: Plos Biologymentioning
confidence: 70%
“…Kir2.1 was reported to stabilize the resting V m of many cell types including cardiac myocytes (Sakmann and Trube, 1984), vascular smooth muscle cells (Karkanis et al, 2003;Park et al, 2008;Quayle et al, 1993), endothelial progenitor cells (Quayle et al, 1993;Zhang et al, 2019) and microglial cells (Gattlen et al, 2020). We rst adopted a real-time dynamic detection of peritoneal macrophage V m for 3 min by patch clamp experiments because of a relatively slow inhibitory effect of ML133 on Kir2.1 (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that K channel activation and hyperpolarization is critical for microglial motility 27,59 . In addition, spinal microglia reactivity is correlated with K channel activation in neuropathic pain 60,61 . Therefore, these results suggest membrane hyperpolarization (associated with K channels) instead of depolarization in microglia may activate microglia, likely due to the increase of Ca 2+ driving force.…”
Section: Discussionmentioning
confidence: 99%